Seven Actions Towards Advancing Patient Authorship and Collaboration in Peer-Reviewed Publications - Bharadia, Trishna; Geissler, Jan; Robson, Rosie; Laštíková, Lucie; Porter, Laura D; Richmond, Grace; Johnson, Ben; Roch, Louise; Toroser, Dikran (The patient, 2025)
Partnerships between patients and the medical research community are strengthening. Patient involvement in research processes through collaborative workstreams provides authentic insights and perspectives, enhances trust between stakeholders and the patient community, brings balance to authorship groups and adds value and contextualisation to publications. Here, patient advocates, representatives from patient and caregiver communities and pharmaceutical and medical communications professionals propose seven actions to advance patient authorship and collaboration in peer-reviewed publications. Drawing on research, personal experience and professional insight, they call for a shift in conventional publication development practices-from seeking reasons to include patient authors to requiring justification for their exclusion-thereby facilitating greater inclusion and representation of the patient voice. The authors advocate moving beyond the concept of 'patient-centricity' towards 'patient partnership' to reflect a collaborative approach and more equitable balance of power and benefits among stakeholders. They also emphasise the importance of involving patients holistically in publication steering committees to ensure that the publication landscape includes patient perspectives and represents lived experiences. Continued facilitation and strengthening of partnerships between patient and non-patient authors is noted as essential for improving communication, understanding and equity within authorship groups. To support the visibility and recognition of patient authors, they recommend the use of the 'patient author' affiliation metatag to better identify, search, filter and standardise publications with patient involvement, identify patient authors and help build an evidence base from which best practice and guidance can be developed. Additionally, the authors highlight the need to consider and develop guidance around compensation of patient authors to acknowledge the contribution and time commitments across the research process and enable greater diversity, equity and inclusion. Finally, they stress the importance of extending the reach of publications to wider audiences through enhanced accessibility formats and open access.